Experimental study on the effect of coal composition on the activation energy of sponge iron reduction - Sabuki, Sabuki; Khairil, Khairil; Sofyan, Sarwo Edhy (Jurnal Polimesin, 2026)
The increasing demand for steel in Indonesia necessitates the development of efficient and sustainable ironmaking technologies. Direct reduction has emerged as a promising alternative to conventional blast furnace processes due to its lower operating temperature and reduced carbon emissions. This study examines the effect of coal composition on the reduction kinetics and activation energy of iron ore briquettes produced from locally sourced raw materials. Briquettes were prepared using Lhoong iron ore (93.88 wt% Fe2O3), sub-bituminous coal from Nagan Raya, and natural rubber latex as a binder. Four composition ratios were investigated: 80:15:5, 75:20:5, 70:25:5, and 60:35:5 (iron ore:coal:binder), each with a total mass of 60 g. Reduction experiments were conducted at 800 °C, 900 °C, and 1000 °C in an LPG-fired furnace. Mass loss was continuously monitored at 2-minute intervals using a digital balance connected to data acquisition software.